2021
DOI: 10.1038/s41598-021-83548-8
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic analysis and QTL mapping of yield and fruit traits in bitter gourd (Momordica charantia L.)

Abstract: Bitter gourd (Momordica charantia L.) is an economically important vegetable crop grown in tropical parts of the world. In this study, a high-density linkage map of M. charantia was constructed through genotyping-by-sequencing (GBS) technology using F2:3 mapping population generated from the cross DBGy-201 × Pusa Do Mausami. About 2013 high-quality SNPs were assigned on a total of 20 linkage groups (LGs) spanning over 2329.2 CM with an average genetic distance of 1.16 CM. QTL analysis was performed for six maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 65 publications
(64 reference statements)
2
15
0
Order By: Relevance
“…While genetic and QTL studies have been widely reported for some cucurbit, crops such as cucumber ( Wei et al, 2016 ; Win et al, 2017 ), bottle gourd ( Wu et al, 2017 ), pumpkin ( Zhang et al, 2015 ), watermelon ( Guo et al, 2015 ; Zhang et al, 2016 ; Gao et al, 2018 ), and melon ( Chang et al, 2017 ; Daley et al, 2017 ; Sheng et al, 2017 ), such studies for bitter gourd, a non-model plant, were very limited. To date, there have been a few reports on the identification of QTLs for horticulture traits in bitter gourd ( Kole et al, 2012 ; Wang and Xiang, 2013 ; Cui et al, 2018 ; Rao et al, 2018 , 2021 ). In the present study, we identified a total of 50 putative QTLs located on 10 chromosomes using the F 4 population from Punjab-14 and PAUBG-6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While genetic and QTL studies have been widely reported for some cucurbit, crops such as cucumber ( Wei et al, 2016 ; Win et al, 2017 ), bottle gourd ( Wu et al, 2017 ), pumpkin ( Zhang et al, 2015 ), watermelon ( Guo et al, 2015 ; Zhang et al, 2016 ; Gao et al, 2018 ), and melon ( Chang et al, 2017 ; Daley et al, 2017 ; Sheng et al, 2017 ), such studies for bitter gourd, a non-model plant, were very limited. To date, there have been a few reports on the identification of QTLs for horticulture traits in bitter gourd ( Kole et al, 2012 ; Wang and Xiang, 2013 ; Cui et al, 2018 ; Rao et al, 2018 , 2021 ). In the present study, we identified a total of 50 putative QTLs located on 10 chromosomes using the F 4 population from Punjab-14 and PAUBG-6.…”
Section: Discussionmentioning
confidence: 99%
“…Each horticulture trait was associated with an average of 5.5 QTLs. Recently, an average of 3 QTLs for six traits (fruit length, fruit diameter, fruit weight, fruit flesh thickness, number of fruits per plant, and yield per plant) in bitter gourd were reported by Rao et al (2021) . In cucurbits, an average of 4–6 QTLs for quantitative traits has been identified in many reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qi [ 7 ] constructed a four-generation population using muskmelon and cantaloupe as parents, and clarified that the melon stem diameter was inherited by two pairs of additive-dominant-epistatic major genes and additive-dominant polygenic genes. Rao [ 8 ] conducted a genetic analysis of the stem diameter of bitter gourd, and found that the inheritance of stem diameter conformed to the additive-dominant-epistatic polygenic genetic model. Lin [ 9 ] constructed a linkage group of chieh-qua, and detected one QTL of the chieh-qua stem diameter on LG2, with the phenotypic variation rate of 10.3%.…”
Section: Introductionmentioning
confidence: 99%
“…The most robust markers can then be employed for marker-assisted selection (MAS). However, the accuracy with which genetic maps are constructed is dependent on the mapping population since doubled haploid (DH) lines, near-isogenic lines (NILs), recombinant inbred lines (RILs), and backcross lines are extremely effective yet to date labour-intensive and time-consuming to generate (Rao et al 2021). GS has been highlighted as a powerful option for selecting polygenic traits that are di cult to select through MAS.…”
Section: Introductionmentioning
confidence: 99%